POLA BAKTERI DAN TES KEPEKAAN ANTIBIOTIKA WANITA HAMIL DENGAN BAKTERIURIA ASIMTOMATIS - L. P. Kalalo; B. Subagjo; Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
Asymptomatic bacteriuria is defined as bacteriuria consisting of one type of bacteria ³ 105 CFU/mL in clean-voided midstreamculture of a person without any symptoms of urinary tract infection. Untreated asymptomatic bacteriuria is dangerous for pregnancybecause complications such as pyelonephritis, maternal sepsis, premature birth, and premature rupture of the membrane, low birthweight baby, hypertension and or preeclampsia, anaemia in pregnancy, amnionitis and post delivery endometriosis can arise. Someasymptomatic cases could threaten the pregnant woman and her foetus without prior pyelonephritis symptoms. The purpose of this studywas to determine the pattern of bacteria in asymptomatic bacteriuria pregnant women and their antibiotic sensitivity. This study hasbeen carried out between October 2003 and April 2004 on 376 pregnant women without symptoms of urinary tract infection. Screeningwas performed using urine culture, followed by antibiotic susceptibility test. The study showed that the prevalence of asymptomaticbacteriuria among pregnant women in RSU Dr. Soetomo was 9.85% (37 out of 376 pregnant women without urinary tract infection).Thirteen bacterial types were found in those 37 positive samples. The most common bacteria found was Escherichia coli (37.83%). Thisbacterium was sensitive to ceftriaxone (85.71%), nitrofurantoin (64.28%) and amoxicillin-clavulanic acid (57.14%). Based on the datagained in this study, it is concluded that the prevalence of pregnancy cases with asymptomatic bacteriuria in the Dr. Soetomo Hospitalis significantly high (9.85%). The most recommended drugs are ceftriaxone, amoxicillin-clavulanic acid and nitrofurantoin.